Synthesis of novel benzenesulfamide derivatives with inhibitory activity against human cytosolic carbonic anhydrase I and II and Vibrio cholerae α- and β-class enzymes - Silvia Bua; Emanuela Berrino; Sonia Del Prete; Vallabhaneni S. Murthy; Vijayaparthasarathi Vijayakumar; Yasinalli Tamboli; Clemente Capasso; Elisabetta Cerbai; Alessandro Mugelli; Fabrizio Carta; Claudiu T. Supuran (Taylor & Francis Group, 2018)
The synthesis of a new series of sulfamides incorporating ortho-, meta, and para-benzenesulfamide moieties is reported, which were investigated for the inhibition of two human (h) isoforms of the zinc enzyme carbonic anhydrase (CA, EC 4.2.1.1), hCA I and II, and two Vibrio cholerae enzymes, belonging to the α- and β-CA classes (VchCAα, VchCAβ). The compounds were prepared by using the "tail approach", aiming to overcome the scarcity of selective inhibition profiles associated to CA inhibitors belonging to the zinc binders. The built structure-activity relationship showed that the incorporation of benzhydryl piperazine tails on a phenyl sulfamide scaffold determines rather good efficacies against hCA I and VchCAα, with several compounds showing KIs < 100 nM. The activity was lower against hCA II and VchCAβ, probably due to the fact that the incorporated tails are quite bulky. The obtained evidences allow us to continue the investigations of different tails/zinc binding groups, with the purpose to increase the effectiveness/selectivity of such inhibitors against bacterial CAs from pathogens, affording thus potential new anti-infectives.